Entrance to the Garbhagriha of the Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
A closer view of the opening that leads into the garbhagriha (sanctum sanctorum) of the Chaunsath Yogini Temple. This entrance is marked by a simple doorframe/architrave that does not have many vertical divisions. The lower portion of the architrave has dvarapalas (door attendants) on either side and river goddesses. The threshold has an ornate mandaraka. Likewise, the lintel of the doorframe has three divinities in framed niches. The empty space above the doorframe constitutes a part of the interiors of the shikhara (superstructure).